Chapter Le marche di lista in russo. Segnali riformulativi, estensivi, generalizzanti... i vse takoe - Benigni, Valentina (Biblioteca di Studi Slavistici, 2016)
This paper offers a survey of list markers in contemporary Russian, i.e. discourse markers that signal the presence of a list and fulfil specific semantic and pragmatic functions, such as generalization (и все такое 'and things like that'), exemplification (типа 'such as/kind of') or reformulation of the list content (так сказать 'so to speak'). It also explores the structural and functional properties of general extenders within the framework of CxG, focusing particularly on the process of lexicalization and grammaticalization of the discourse marker и все такое 'and things like that'.